JSFA reports (John Wiley & Sons, 2021)
Publishes peer-reviewed original research, reviews, and perspectives in these areas, with particular emphasis on interdisciplinary studies at the agriculture/ food interface, Publisher website, viewed Sept. 2, 2022.